Implementation and integration of a multidisciplinary pharmacogenomics service in an underserved integrated behavioral health clinic - Alghamdi, Bader M.; Rogers, Sara; Roberman, Susan; Williamson, Meredith; Panahi, Ladan (Frontiers in Pharmacology, 2025)
ObjectiveTo assess the feasibility and impact of incorporating a multidisciplinary pharmacogenomics (PGx) service within an underserved behavioral health clinic, with an emphasis on clinician perceptions.MethodologyThis study was conducted in two phases at the Texas A&M Family Care Clinic. Phase one involved an online cross-sectional survey of the multidisciplinary clinic team to assess their knowledge, attitudes, and readiness for PGx integration. Phase two detailed the development and implementation of a PGx service within the Integrated Behavioral Health (IBH) clinic, outlining the workflow and collaborative approach used to offer genetic testing to eligible patients.Key findingsOf the 23 survey participants, 91% believed the PGx service would positively impact patient care, and 87% expressed interest in receiving PGx-related training. Confidence in pharmacists’ ability to lead the service was reported by 65% of respondents. The primary concerns identified included cost of care, clinical utility, and potential workflow disruptions. A collaborative implementation model was developed, including preemptive and reactive testing pathways.ConclusionThe implementation of a pharmacist-driven PGx service in an underserved behavioral health clinic was well-received by the clinical team and deemed feasible. While concerns regarding resources and workflow were noted, strong interest in training and multidisciplinary collaboration highlights the potential for scalable PGx service models in similar settings.